Contribution of Time and Income of Women Stick Craftsmen in Households in Tualang District, Siak Regency (Case Study: Oil Palm Stick Craft Woman in Tualang Timur Village) - Bambang Suardi; Yulia Andriani (Indonesian Journal of Agricultural Economics, 2022)
This research aims to describe the profile of oil palm sticks agroindustry, describe the profile of women crafts in the oil palm sticks industry, find out the time allocation, and the contribution of women palm oil stick craftsmen, and analyze the contribution of women's income from the sticks agroindustry business households in Tualang Timur village, Tualang district Siak regency. The research method used is the census method. The data used are primary data and secondary data. Informants in this study were all members of the women's group of oil palm stick craft in Tualang Timur village Tualang district Siak regency. The results of this research indicate that the largest time allocation for women is on productive activities of 42 hours per week and the smallest time allocation for social activities is 0.85 hours per week. The average acceptance of women as owners as well as craft is Rp. 1,331,400 per month. When viewed from family income, it turns out that the income of the owner's family is greater, where the average income of the owner's family is Rp. 4,856,400 per month. So it can be seen that the contribution of women is 27.41 percent in family income